Recruitment of Community-Residing Youth Into Studies on Aggression - Cheney, Rose Ann (Journal of community psychology, 2013)
Recruitment of community-based youth into studies is challenging. We examined access issues, minority status, and personal costs of participation for a study of children with aggressive behaviors, designed to identify which ones are at risk for future violent behaviors, to identify protective factors, and to test interventions to reduce aggression. Of 1,038 contacts, 112 declined, 239 could not be re-contacted, and 124 were ineligible. Three hundred and fifty of 563 scheduled child-parent dyads completed intake assessment. Most were recruited through targeted mailings (33%) and community flyers (22%), 12% through regional news advertisement, 8% by Craigslist, and 5% through healthcare providers/clinics. Factors contributing to enrollment rates by zip code showed the percentage of Black residents per zip code and targeted mailings positively contributed (Beta = .200 & .419, respectively) and estimated transit travel time negatively contributed (Beta =.299) to enrollment rates (R2 = 0.562). Targeted mailings proved to be the most efficient strategy in successful recruitment